A Mixed Component Supramolecular Hydrogel to Improve Mice Cardiac Function and Alleviate Ventricular Remodeling after Acute Myocardial Infarction. (17th July 2017) - Chen, Guoqin; Li, Jinliang; Song, Mingcai; Wu, Zhiye; Zhang, Wenzhu; Wang, Zhongyan; Gao, Jie; Yang, Zhimou; Ou, Caiwen
Abstract : Myocardial infarction (MI) remains the major cause of death and disability in the world, and intramyocardial administration of biomaterials (e.g., hydrogels) along the perimeter of MI region is demonstrated as an effective way for the treatment of MI. The curcumin has anti‐inflammation, antioxidation, and antiapoptosis properties, and nitric oxide (NO) molecules are favorable for angiogenesis. This study prepares a mixed component hydrogel capable of releasing both bioactive curcumin and NO for the treatment of MI. The study shows that the combinational treatment of curcumin and NO can remarkably reduce collagen deposition, improve cardiac function, ameliorate adverse myocardium remodeling, suppress apoptosis, and hypertrophy as well as attenuate the expression of matrix metalloproteinases (MMPs) and transforming growth factor‐β1 (TGF‐β1) and upregulate the expression of silent information regulator 1 than curcumin alone, because of the synergistic action of both molecules and the angiogenesis promotion ability of NO. The results indicate that codelivery of curcumin and NO in a controllable manner by hydrogels might be considered as a promising option for treatment of cardiovascular disease. Abstract : A two component hydrogel capable of releasing both nitric oxide and curcumin to improve mice cardiac function and alleviate ventricular remodeling after acute myocardial infarction is presented.